The role of leadership style in improving organizational performance - Agustina Agustina; Roby Sambung; Yunikewaty Yunikewaty (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
This study aims to explain the strategy of human resources (SHR) in mediating leadership styles in improving performance and to identify the dominant leadership style in influencing SHR. 96 echelon officials were used as samples with a stratified random sampling approach. The results show that all hypotheses are proven to be influential, and SHR is a mediation complementary to partial mediation. This study provides a unique development where transformational leadership is the dominant factor in improving SHR compared to visionary leadership.